Literature Review: Immunopathobiology of AIDS-related Kaposi’s Sarcoma - Rahmadani, Nia Ardelia (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Kaposi's Sarcoma (KS) is an angioproliferative malignancy closely associated with Acquired Immunodeficiency Syndrome (AIDS), primarily caused by Human Herpesvirus 8 (HHV-8) infection in individuals with immunosuppression due to Human Immunodeficiency Virus (HIV). The reduction of CD4⁺ T cells by HIV causes cellular immunity disorders that allow HHV-8 to survive in both latent and lytic phases and trigger tumor formation through immune system modulation. This review aims to understand the immunopathobiology of AIDS-related KS. This study is a narrative literature review compiled from various scientific articles obtained from PubMed, Google Scholar, and ScienceDirect. Various literature indicates that HHV-8 is able to evade the immune response by suppressing the Toll-like receptor (TLR) pathway, reducing Major Histocompatibility Complex (MHC) expression, and producing cytokine and chemokine homologs that support the tumor microenvironment. Immunosuppression due to HIV further strengthens these mechanisms and plays an important role in the formation of KS lesions. Understanding the immunopathobiology mechanisms of AIDS-related KS provides a scientific basis for the development of more effective prevention, early detection, and immunomodulatory therapy strategies in the future.